Cross Cultural Adaptation of the Cultural Formulation Interview-Patient Version (Contemporary Journal of Social Science Review, 2024)
Objective: The current study attempted to translate and adapt the Cultural Formulation Interview (CFI)-Patient Version from English into the national language, Urdu, and to guarantee the validity and reliability of measurements in Pakistani cultural and linguistic contextsDesign: Cross-Cultural Translation design / Structured interviewPlace and Duration of Study: Lahore, Pakistan, March2024-August2024Subject and Method: Pilot testing participants (N = 2), who are men (n = 1) and women (n = 1) with MDD diagnosis, will be selected via purposive sampling to examine gender differences with mild to moderate major depressive disorder. Two stages comprise the current research. Translations of the original Cultural Formulation Interview (CFI) Patient Version into forward and back translations, which are highly implied, were done in the initial step. Inter-rater reliability and content validity of translated interviews were carried out. Adaptation of translated Cultural formulation interview on the pilot sample.Result and Conclusion: The results demonstrate sufficient reliability and validity. Pakistan's national language is Urdu. Most people in Pakistan can grasp Urdu but have trouble understanding and comprehending English. This is the primary reason the interview has been translated into Urdu: to get more accurate and verified measurements for Pakistani citizens in their mother language.